Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Let f be a differentiable function with f(-1) = -5 and f'(-1) = -1. Let the function g(x) = x² f(x). Write the equation of the line tangent to the graph of g at the point where x = -1.

Sagot :

Answer:

[tex]y=9x+4[/tex]

Step-by-step explanation:

Differentiation is an algebraic process that finds the gradient of a curve.

At a point, the gradient of a curve is the same as the gradient of the tangent line to the curve at that point.

Given function:

[tex]g(x)=x^2 \:f(x)[/tex]

Differentiate the given function using the product rule.

[tex]\boxed{\begin{minipage}{5.5 cm}\underline{Product Rule for Differentiation}\\\\If $y=uv$ then:\\\\$\dfrac{\text{d}y}{\text{d}x}=u\dfrac{\text{d}v}{\text{d}x}+v\dfrac{\text{d}u}{\text{d}x}$\\\end{minipage}}[/tex]

Identify u and v and differentiate them with respect to x:

[tex]\text{Let $u=x^2 \implies \dfrac{\text{d}u}{\text{d}x}=2x$}[/tex]

[tex]\text{Let $v=f(x) \implies \dfrac{\text{d}v}{\text{d}x}=f'(x)$}[/tex]

Put everything into the product rule formula:

[tex]\begin{aligned}\implies \dfrac{\text{d}y}{\text{d}x} & =u\dfrac{\text{d}v}{\text{d}x}+v\dfrac{\text{d}u}{\text{d}x}\\& = x^2 \cdot f'(x)+f(x) \cdot 2x\\& = x^2\:f'(x)+2x\:f(x)\end{aligned}[/tex]

Given:

[tex]f(-1)=-5[/tex]

[tex]f'(-1)=-1[/tex]

To find the gradient of the curve at x = -1, substitute x = -1 into the differentiated function:

[tex]\begin{aligned}x=-1 \implies \dfrac{\text{d}y}{\text{d}x} & =(-1)^2\:f'(-1)+2(-1)\:f(-1)\\& =(1)(-1)+(-2)(-5)\\& =-1+10\\& =9\end{aligned}[/tex]

Therefore, the gradient of the curve at x = -1 is 9.

[tex]\begin{aligned}\textsf{When $x = -1$} \implies g(-1)&=(-1)^2 \cdot f(-1)\\& = 1 \cdot (-5)\\& = -5\end{aligned}[/tex]

Therefore, the point on the function is (-1, -5).

Substitute the found gradient and the point into the point-slope form of a linear equation:

[tex]\begin{aligned}y-y_1 & =m(x-x_1)\\\implies y-(-5)&=9(x-(-1))\\y+5&=9(x+1)\\y+5&=9x+9\\y&=9x+4\end{aligned}[/tex]

Therefore, the equation of the line tangent to the graph of g at the point where x = -1 is:

[tex]\boxed{y=9x+4}[/tex]

We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.